P165 Association between vitamin D deficiency and extended duration of COVID-19 symptoms. (11th November 2022) - Roberts, SA; Lugg, ST; Faniyi, AA; Faustini, SE; Faniyi, C; Duffy, J; Hewison, M; Shields, A; Richter, AG; Parekh, D; Scott, A; Thickett, DR
Abstract : Introduction and Objectives: Vitamin D (VD) is involved in immunity and inflammation through mechanisms such as renin inhibition and inflammatory cytokine reduction. There is already evidence to suggest that VDD may increase COVID-19 infection susceptibility, however research assessing the impact of VDD on COVID-19 symptom duration is limited. The aim of this research was to determine whether VDD is a significant independent risk factor for extended durations of COVID-19 symptoms. Methods: The study included 392 healthcare workers who isolated due to COVID-19 symptoms during the first wave of the pandemic (12th to 22nd May 2020) as part of the convalescent immunity (COCO) study. Data on 8 symptom types and duration of symptoms were collected, including patients' demographics and co-morbidities. Anti-SARS-Cov-2 antibodies were measured using a combined IgG, IgA and IgM ELISA (The Binding Site). Vitamin D status was determined by measurement of serum 25(OH)D3 using the AB SCIEX Triple Quad 4500 mass spectrometry system. VDD was defined as serum 25(OH)D3 <30 nmol/L. Results: Through univariate analysis of VDD and non-VDD staff, we initially showed VDD to be significantly associated with longer durations of body aches (median 7 days, IQR 5–14 vs. median 5 days, IQR 3–7.5; p=0.0075) and fatigue (median 12 days, IQR 7–14 vs. median 7 days, IQR 4–14; p=0.0127). VDD did not influence the duration of the other 6 symptoms analysed, such as cough and fever. Using binary logistic regression models, we confirm that VDD is a significant independent risk factor for extended durations of fatigue (OR 2.089, 95% CI 1.087–4.011; p=0.027) and body aches (OR 3.069, 95% CI 1.538–6.124; p=0.001). Additionally, VDD staff experienced a significantly greater quantity of symptoms compared to non-VDD staff (median 5, IQR 4–7 versus median 4, IQR 3–6; p=0.0030). Conclusions: This is one of the first studies to investigate the influence of VDD on COVID-19 symptom duration. Our results indicate that VDD is a significant independent risk factor for a longer duration of body aches and fatigue. Larger studies are required to confirm these results and determine if VD supplementation could shorten symptoms.